Effect of Centella Asiatica Powder (gotu kola) Against Stretch Marks in Postpartum Mothers - Sanna, Alfrida; Hendriani, Dwi; Firdaus, Rivan (Rifa'Institute, 2024)
Introduction: Stretch marks are one of the inconveniences during pregnancy and the puerperium. Stretch marks, also known as striae gravidarum, are anatomical and physiological changes during pregnancy that can occur in the abdomen, breasts and thighs. It is often also found in the areola or vaginal areas that experience hyperpigmentation. Objective: The aim is to find out the effect of Cantella Asiatica Powder (Gotu Kola) on Stretch Marks in Postpartum Mothers at Gerbang Sehat Mahulu Hospital in 2023. Method: the type of research is quasi-experimental research, with a non-equivalent control group design approach. Sampling technique with purposive sampling. Data analysis Using Paired Sample T Test. Results and Discussion: Based on the results of the study the intervention group and the control group had the appearance of real stretch marks, namely 10 (100%). After administration of Centella Asiatica (gotu kola) powder, most of the respondents had faint stretch marks, 9 (90.0%). Whereas in the control group, after health education about stretch marks, there were 7 (70.0%) respondents who had visible stretch marks and 3 (30.0%) respondents who had faint stretch marks. Conclusion: There is an effect of centella asiatica powder (gotu kola) on stretch marks in postpartum women